Urokinase Excretion in Health and its Alteration in Certain Disease States - Smyrniotis, Fotios E; Fletcher, Anthony P; Alkjaersig, Norma; Sherry, Sol (Thrombosis and Haemostasis, 1959)
1. Urokinase excretion rates in normal subjects were found to be independent of age, sex and urine volume.2. Urokinase excretion rates were found to be raised following the onset of myocardial infarction (p < 0.001) and after an attack of coronary insufficiency (p = 0.02). Excretion rates were depressed in patients suffering from carcinomatosis (p < 0.001), congestive cardiac failure (0.05 < p < 0.1) and uremia (p < 0.001).3. These differences suggest that significant alterations in the plasma fibrinolytic system may result as a consequence of disease states.